2019
DOI: 10.22358/jafs/105132/2019
|View full text |Cite
|
Sign up to set email alerts
|

Removal of fat from crushed black soldier fly larvae by carbon dioxide supercritical extraction

Abstract: The larvae of the black soldier fly, Hermetia illucens, contain high amounts of protein and fat, and so are a good feed source. However, this high fat content hinders the production of such feed. The excess fat must thus be removed to enable the larvae to be used as a feedstock e.g., for aquaculture and livestock. Firstly, the use of hot water treatment as a strategy for extracting fat from dried larvae was tested. It was found that this process reduced the fat content of the raw material (from 30 to about 16%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Kierończyk et al (2020) used SC-CO2 to extract the fat from H. illucens with 300 bar and a temperature of 40°C. Furthermore, Kim et al, 2019, showed that the SC-CO2 extraction method could be an effective method for the defatting of H. illucens (HI) meals subjected to 10-18 mesh crushing at 350 bar for 6 h. A 95% fat extraction yield was achieved.…”
Section: Insect Lipids: An Overviewmentioning
confidence: 99%
“…Kierończyk et al (2020) used SC-CO2 to extract the fat from H. illucens with 300 bar and a temperature of 40°C. Furthermore, Kim et al, 2019, showed that the SC-CO2 extraction method could be an effective method for the defatting of H. illucens (HI) meals subjected to 10-18 mesh crushing at 350 bar for 6 h. A 95% fat extraction yield was achieved.…”
Section: Insect Lipids: An Overviewmentioning
confidence: 99%
“…However, further optimization of the supercritical carbon dioxide process, especially with the use of a co-solvent, might improve the extraction yield in future work . The choice of lipid extraction method impacts protein extraction, and successful defatting and protein precipitation are important for obtaining good yields and purifications of extracted insect chitin …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the defatting process required when using BSFL as feed was tested in Korea using hot water and supercritical CO 2 extraction [46]. When BSFL defatting was performed using hot water, the fat content in BSFL was reduced to 16%.…”
Section: Republic Of Koreamentioning
confidence: 99%
“…In contrast, when the supercritical CO 2 extraction method was used, the fat content in BSFL was reduced to 5% or less. Therefore, it was concluded that the supercritical CO 2 extraction method may be a suitable method for the defatting of BSFL for its use as feed [46].…”
Section: Republic Of Koreamentioning
confidence: 99%
See 1 more Smart Citation